(untitled) (Indian Journal of Public Health Research & Development, 2020)
Puerperal infection is inflammation of all genitalia in the puerperium caused by aerobic and anaerobic bacteria, one of which is Stapylococcus aureus which can attack and survive in epithelial cells and endothelial cells, then recognized by the Precenting Cell Antigen (APC). The APC will secrete cytokines as triggers for the activation of Thais, Th1, Th2, Treg and Th17. Interleukin-23 (IL 23). The purpose of this study was to prove the effect of L. reuteri probiotics on increasing levels of IL-23 cytokines in puerperal mice induced by S. aureus on the first days. True Experimental research method post test Only Control group in vivo 40 tails Balb/c pregnant 10th day was divided into 4 groups K-, K+, P1, P2. Then performed surgery to take blood from the heart which will then produce blood plasma after centrifugation followed by measurement of IL 23 levels by the ELISA kit method with no. Catalog M2300 R & D brand Analysis of data using the Independent Sample T Test with the help of SPSS For Windows 23 software. The results of the comparison between the negative control (K-) with the treatment group on the first day proved that an increase in IL 23 cytokine levels occurred, a comparison between groups observation on the first day proved to be an increase in IL 23 cytokine levels, the results of a comparison test between P1 and P2 on the first day there was an increase in IL 23 cytokine levels an increase but not statistically significant the administration of L. reuteri probiotics can increase the levels of cytokines IL 23 in puerperal mice induced by S. aureus therefore probiotics can be useful in the puerperium to increase body immunity to prevent infection during the puerperium